The Cambridge handbook of international and comparative trademark law / edited by Irene Calboli, Jane C. Ginsburg. - Calboli, Irene; Ginsburg, Jane C. (Cambridge University Press, 2020)
Trade in goods and services has historically resisted territorial confinement, but trademark protection remains territorial, albeit within an increasingly important framework of multilateral treaties. Trademark law therefore demands that practitioners, policy-makers and academics understand principles of international and comparative law. This handbook assists in that endeavour, with chapters describing and critically analyzing international and regional frameworks, and providing comparative perspectives on the substantive issues in trademark law and related fields, such as geographic indications, advertising law, and domain names. Chapters contrast common law and civil law approaches while focusing on the US and EU trademark systems in light of the role these systems have played in the development of trademark laws. Additionally, this handbook covers other jurisdictions, both common law and civil law, on the Asia-Pacific, African, and South American continents. This work should be read by anyone seeking a better understanding of trademark law around the world.